Clinical effectiveness and cost-effectiveness of the Rehabilitation Enablement in Chronic Heart Failure (REACH-HF) facilitated self-care rehabilitation intervention in heart failure patients and caregivers: rationale and protocol for a multicentre randomised controlled trial. Issue 12 (23rd December 2015) - Taylor, R S; Hayward, C; Eyre, V; Austin, J; Davies, R; Doherty, P; Jolly, K; Wingham, J; Van Lingen, R; Abraham, C; Green, C; Warren, FC; et al.
Abstract : Introduction: The Rehabilitation EnAblement in CHronic Heart Failure (REACH-HF) trial is part of a research programme designed to develop and evaluate a health professional facilitated, home-based, self-help rehabilitation intervention to improve self-care and health-related quality of life in people with heart failure and their caregivers. The trial will assess the clinical effectiveness and cost-effectiveness of the REACH-HF intervention in patients with systolic heart failure and impact on the outcomes of their caregivers. Methods and analysis: A parallel two group randomised controlled trial with 1:1 individual allocation to the REACH-HF intervention plus usual care (intervention group) or usual care alone (control group) in 216 patients with systolic heart failure (ejection fraction <45%) and their caregivers. The intervention comprises a self-help manual delivered by specially trained facilitators over a 12-week period. The primary outcome measure is patients' disease-specific health-related quality of life measured using the Minnesota Living with Heart Failure questionnaire at 12 months' follow-up. Secondary outcomes include survival and heart failure related hospitalisation, blood biomarkers, psychological well-being, exercise capacity, physical activity, other measures of quality of life, patient safety and the quality of life, psychological well-being and perceived burden of caregivers at 4, 6 and 12 months' follow-up. A process evaluation will assess fidelity of intervention delivery and explore potential mediators and moderators of changes in health-related quality of life in intervention and control group patients. Qualitative studies will describe patient and caregiver experiences of the intervention. An economic evaluation will estimate the cost-effectiveness of the REACH-HF intervention plus usual care versus usual care alone in patients with systolic heart failure. Ethics and dissemination: The study is approved by the North West—Lancaster Research Ethics Committee (ref 14/NW/1351). Findings will be disseminated via journals and presentations to publicise the research to clinicians, commissioners and service users. Trial registration number: ISRCTN86234930; Pre-results.